Immediate Anatomic Results after the Endovascular Treatment of Ruptured Intracranial Aneurysms: Analysis in the CLARITY Series - Pierot, L. (AJNR Am J Neuroradiol, 2010)
BACKGROUND AND PURPOSE: The efficacy of the endovascular treatment in providing stable occlusion of intracranial aneurysms is still controversial and should be precisely analyzed. A first step is to carefully study immediate anatomical results. CLARITY (Clinical and Anatomical Results in the Treatment of Ruptured Intracranial Aneurysms) is a prospective multicenter consecutive series including patients treated by coiling for ruptured aneurysms. Immediate anatomic results are presented. MATERIALS AND METHODS: Postoperative anatomic results were evaluated by DSA by the treating physician and anonymously and independently by 2 experienced neuroradiologists by using the 3-point Montreal Scale. Patients were divided into 2 groups: patients treated with GDC and those treated with Matrix detachable coils. RESULTS: A total of 773 patients (461 women, 312 men; 19–80 years of age; mean, 51.2 ± 13.2 years) with 773 ruptured aneurysms were included in the study. The rate of occlusion as determined by the treating physician was designated complete for 586 aneurysms (75.8%), neck remnant for 145 aneurysms (18.8%), and aneurysm remnant for 42 aneurysms (5.4%). The same evaluation as reported by the 2 independent reviewers was complete occlusion for 366 aneurysms (47.4%), neck remnant for 324 aneurysms (41.9%), and aneurysm remnant for 83 aneurysms (10.7%). Postoperative anatomic results were significantly linked to age but not to the technique of endovascular treatment or aneurysm characteristics (location, size, dome-to neck ratio). Results were not significantly different between the GDC and Matrix group. CONCLUSIONS: Endovascular treatment of ruptured intracranial aneurysms resulted in a high rate of satisfactory occlusion (complete occlusion and neck remnant in 89.3%). Patient age was the only factor associated with the rate of occlusion. The rate of aneurysm occlusion differed insignificantly between GDC and Matrix coils.